Debate: Mentalising remotely – The AFNCCF's adaptations to the coronavirus crisis. Issue 3 (5th July 2020) - Fonagy, Peter; Campbell, Chloe; Truscott, Alexandra; Fuggle, Peter
Abstract : An overview of the work the approach taken by the Anna Freud National Centre for Children and Families in the rapid transition to remote working in response to the coronavirus lockdown. We outline some of the challenges of remote working and how we are seeking to mitigate them, informed by the over‐riding principle that individual relationships and the experiences of the child, young person and family must remain the central concern. The importance of maintaining a mentalising stance in remote working is discussed. We argue that a mentalising relationship which generates epistemic trust is possible in remote working, but this will require particular thought and effort on the part of the therapist. In particular, it is suggested that mentalising processes can be supported in remote working through, in the absence of the more implicit communications that are possible in face‐to‐face work, more explicit communications about mental states.